Modalitas Terapi Striae - Ambar Aliwardani; Putti Fatiharani Dewi; Fiska Rosita; Indah Julianto (PT Dexa Medica, 2023)
Striae or strechmark is a form of benign skin lesion manifested as inflammatory streaks perpendicular to the direction of skin tension which has cosmetic morbidity and possesses risk of secondary infection in severe case. Various therapeutic modalities have been introduced, such as topical therapy, physical therapy using devices, lasers, and the latest is celullar therapy using platelet-rich plasma. Such varied treatment modalities are reported to have varied results.